MSRG Bibliography 2019–2021 - Dyer, Christopher (Medieval Settlement Research, 2023)
This list includes books and articles on British and Irish settlement between the fifth and fifteenth centuries, published in 2019, 2020 and 2021, with the works of each year separately recorded. Books from continental Europe are included if they have some British or Irish content. The 2019 list includes some items (mainly from 2018) previously omitted. There are bound to be omissions from the three years covered here, and these should be notified to the compiler for future inclusion: cd50@le.ac.uk. The bibliography is focussed on the Group’s specialism of medieval rural settlement. It includes publications deriving from archaeology, place-names, geography and history. It does not attempt to cover works in social, economic, cultural and agrarian history and place-name studies unless they feature settlements. Archaeological work on towns, castles, cemeteries or religious sites, or on artefacts or environmental evidence, are not included, except those explicitly connected to rural settlements.